Using Strategic Management Accounting Methods To Women-Owned Msmes Performance - Tiara, Shita; Irawan, Ari; Ovami, Debbi Chyntia; Ramadhany, Andi Aulya; Lubis, Henny Zurika; Nurlayla, Indah (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
SMA stands for strategic management accounting, which is a collection of related methods and approaches to management that can help with the integration of strategic thinking into management. The purpose of this study is to present strategic management accounting concepts and discuss how they might help women-owned MSMEs in Medan perform better. For the past thirty years, academics and professionals have found great pleasure in discussing the application of high school tools and procedures. This study integrates two scientific domains, specifically management and accounting. This study uses a quantitative, descriptive methodology. This study examines how women-owned MSMEs in Medan City function and how they apply strategic management accounting practices. The results demonstrated that MSMEs supported by IWAPI Medan City performed better when strategic management accounting procedures were implemented.